Investigation on airfoil operating in Ground Effect region - Pillai, Nikhil; T., Anil; Radhakrishnan, Aravind; Vinod, Rahul; Kumar E., Sudheesh; Zaid, Zahir; Jacob, Antony; M., Manojkumar (International Journal of Engineering and Technology, 2014)
The idea of using a wing in ground effect vehicle has been suggested with the objective of developing a very economical and efficient means of rapid transportation across water bodies. This paper investigates into wing in ground effect airfoil geometry. ANSYS is used to perform the CFD analysis of the airfoils. CFD analysis has been performed on various airfoils operating in the ground effect region and a special class of airfoil called DHMTU has been found to have maximum aerodynamic efficiency. The DHMTU studied here is DHMTU 8-40-2-10-3-6-2-15. Aerodynamic efficiency for this particular airfoil has been determined through CFD analysis at various angles of attack. It has been found that the DHMTU possesses superior aerodynamic efficiency at low angle of attack and the maximum aerodynamic efficiency is found at 60 angle of attack. From CFD analysis it has also been determined that as the proximity to the ground reduces, the value of lift increases. The characteristics of this airfoil at various air speeds have also been determined through CFD analysis. These studies have illustrated the unique characteristics of the DHMTU airfoils and indicated areas for further optimization of the design of ground effect airfoils. The use of this airfoil for the ground effect vehicle can further lead to increase in efficiency of the craft.Abbreviations:CFDÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Computational Fluid DynamicsDHMTUÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Department Of Hydro-Mechanics of the Marine Technical UniversityNACAÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â National Advisory Committee on AeronauticsL/DÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Lift to Drag RatioWIGÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Wing in GroundVÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Free stream velocityReÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Reynolds numberÂ h/cÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Height to Chord RatioCLÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Coefficient of liftCDÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Coefficient of dragAOAÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Angle Of Attack